2007
DOI: 10.1016/j.amjcard.2007.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Blood Pressure Response to Trandolapril Add-On Therapy in Patients Taking Verapamil SR (from the International Verapamil SR/Trandolapril [INVEST] Study)

Abstract: Factors such as age and race/ethnicity might influence blood pressure (BP) response to drugs. Therapeutic response to the angiotensin-converting enzyme inhibitor trandolapril used as add-on therapy to stable calcium channel blocker therapy with verapamil sustained release 240 mg was addressed in a racially/ethnically diverse group of 1,832 hypertensive patients with coronary artery disease. Furthermore, the association with a polymorphism (1166A→C) in the angiotensin II type 1 receptor gene (AGTR1) was tested.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…The renin-angiotensin system (RAS) plays a major role in blood pressure regulation and electrolyte metabolism 1 ; however, the overactivation of the RAS is thought to play a pivotal role in the pathophysiology of cardiovascular, 2 renal 3 and metabolic conditions. 4 Plasma renin had been associated with cardiovascular morbidity and mortality in hypertensive patients 5 , 6 and recent studies also confirmed that higher plasma renin was associated with greater cardiovascular mortality in patients referred for coronary angiography 7 and in community-based cohort studies. 8 , 9 The plasma renin activity (PRA) is affected by a number of factors, especially quantity of sodium intake.…”
Section: Introductionmentioning
confidence: 90%
“…The renin-angiotensin system (RAS) plays a major role in blood pressure regulation and electrolyte metabolism 1 ; however, the overactivation of the RAS is thought to play a pivotal role in the pathophysiology of cardiovascular, 2 renal 3 and metabolic conditions. 4 Plasma renin had been associated with cardiovascular morbidity and mortality in hypertensive patients 5 , 6 and recent studies also confirmed that higher plasma renin was associated with greater cardiovascular mortality in patients referred for coronary angiography 7 and in community-based cohort studies. 8 , 9 The plasma renin activity (PRA) is affected by a number of factors, especially quantity of sodium intake.…”
Section: Introductionmentioning
confidence: 90%
“…Additionally, genomic DNA samples collected from various self-identified racial and ethnic groups during the course of participation in a large multicenter clinical study of combination antihypertensive treatment (INternational VErapamil SR/Trandolapril Study [INVEST]) were also available for analysis. 15 This group consisted of 355 additional white subjects, 117 black subjects, 299 subjects of Hispanic ethnicity, and 54 Asian individuals. The aberrant metabolizer, his parents, and study peers were not included in the calculation of allelic frequency because a priori information regarding their CES1 activity was known to investigators.…”
Section: Genotyping For Ces1 Variants and Determination Of Snp Frequencymentioning
confidence: 99%
“…Despite less BP reduction with monotherapy with ACEIs and ARBs in Blacks [64], no causal candidate genes including ACE gene insertion/deletion (I/D) polymorphism or angiotensin type 1 receptor, AGTR1 gene, have been conclusively demonstrated [54,65,66]. Moreover, although angioedema with ACE inhibitors is more common in Blacks [67], no specific underlying genetic cause has been elucidated [62].…”
Section: Angiotensin Converting Enzyme Inhibitors and Angiotensin Recmentioning
confidence: 99%